Metformin ameliorates body mass gain and early metabolic changes in ovariectomized rats. Issue 12 (December 2019) - Barthem, Clarissa Souza; Rossetti, Camila Lüdke; Carvalho, Denise P; da-Silva, Wagner Seixas
Abstract : Estradiol has been used to prevent metabolic diseases, bone loss and menopausal symptoms, even though it might raise the risk of cancer. Metformin is usually prescribed for type 2 diabetes mellitus and lowers food intake and body mass while improving insulin resistance and the lipid profile. Ovariectomized rats show increased body mass, insulin resistance and changes in the lipid profile. Thus, the aim of this work was to evaluate whether metformin could prevent the early metabolic dysfunction that occurs early after ovariectomy. Female Wistar rats were divided into the following groups: SHAM-operated (SHAM), ovariectomized (OVX), ovariectomized + estradiol (OVX + E2) and ovariectomized + metformin (OVX + M). Treatment with metformin diminished approximately 50% of the mass gain observed in ovariectomized animals and reduced both the serum and hepatic triglyceride levels. The hepatic levels of phosphorylated AMP-activated protein kinase (pAMPK) decreased after OVX, and the expression of the inactive form of hepatic acetyl-CoA carboxylase (ACC) was also reduced. Metformin was able to increase the levels of pAMPK in the liver of OVX animals, sustaining the balance between the inactive and total forms of ACC. Estradiol effects were similar to those of metformin but with different proportions. Our results suggest that metformin ameliorates the early alterations of metabolic parameters and rescues hepatic AMPK phosphorylation and ACC inactivation observed in ovariectomized rats.